Portraying EFL Students’ English Listening Experiences - Alviaderi Novianti (Musamus Journal of Language and Literature, 2021)
Many studies had been conducted in a large-scale on the investigation on the students’ problems and difficulties in listening comprehension. Most of the studies showed that the difficulties come from the internal factor that is the students’ linguistics ability. The teacher also had tried to implement some solutions regarding to those listening problems, but the students perhaps still found hindrance in getting a good achievement in listening. This study aimed at recognizing the students’ perception on the importance of listening ability and finding out the other factors that could hinder students in dealing with their listening activity. The instruments were questionnaire on students’ difficulties and semi-structured interview. Twenty-three of second-semester students majoring English education were involved as research participant. The rationale of the purposive sampling technique was that students involved were considered as voluntary research participants. The questionnaire was spread to all research participant while semi-structured interview. Three major challenges were found. The students found noises become the biggest factor that could impede the listening activity. Not only the noises, the students’ biases as receiver in listening the information could impede them from comprehending the listening content, as they think that they just need to know the conclusion rather than paying attention to the whole listening content. The result of the interview turned out to be the solution that could be considered by the teacher in overcoming students with the difficulty in English listening activity.